Uneven Implications of Lockdown Amid COVID-19 in India: From Harassment, Stigma, Crime, and Internally Displaced People to Stress and Coping Strategies in the Middle/Upper Class - Shagufta Nasir; Mohammad Ghazi Shahnawaz; Lydia Giménez-Llort (Behavioral Sciences, 2022)
A content analysis of an English Newspaper, The Times of India (the world’s largest newspaper by circulation) during the first national lockdown amid the COVID-19 pandemic identified nine different categories culled out from a total of 129 news categories reporting unprecedented COVID-19 stories. Half of them portrayed two sides of a coin: from daily wagers and migrant workers, including internally displaced people (23/129), harassment and stigma (4/129), and crime (3/129) to stressors and coping strategies for middle/upper class individuals (39/129). Reports evidenced increased vulnerability in the lower layers of Indian stratified society. Yet, two years later, the uneven implications on physical and mental health are scarcely studied by scientific researchers.